Lumbar spinal stenosis: pendekatan tatalaksana bedah - Kevin Giovani Mandua; Alvarez Zefanya Moningka (Intisari Sains Medis, 2022)
Background: Lumbar spinal stenosis (LSS) is the most common subtype of spinal stenosis. This pathologic disorder is the most common cause of low back pain in elderly. LSS can be either congenital or acquired, which the disorder is mainly caused by the degenerative process. Diagnosis of LSS is made by combination of clinical manifestations and radiological findings. Management of LSS may include conservative measures in form of physical therapy, steroid injection on facet joints or epidural space, and also surgical decompression procedure. LSS often reduces invididuals’ quality of life and productivity; hence, it is the most common indication for lumbar spinal canal decompression procedure. Case report: A 41 years old woman complained of low back pain that was referred to the left buttock and leg area. The complaints were also accompanied by numbing sensation on the antero-lateral side of the left leg. Complaints have been felt continuously since 5 months ago. From physical examination, the Visual Analogue Scale (VAS) was 5-6 with positive laseque test on left leg accompanied with hypoesthesia in L4, L5, and S1 dermatome. MRI findings suggested the diagnosis of canalis stenosis of L4-L5 and L5-S1. We perfomed laminectomy and Posterior Lumbar Interbody Fusion (PLIF) on this patient. Conclusion: Surgical approaches are based on the anatomic location, number of segment affected, involvement of thoracolumbar junction, transitional anatomy, instability, and deformity. Factors that affect patients’ clinical outcome after the surgical procedure should be considered before starting the procedure.   Latar belakang: Lumbar spinal stenosis (LSS) merupakan jenis stenosis spinal yang paling sering dijumpai, dimana kelainan ini merupakan salah satu penyebab patologis tersering dari nyeri punggung bawah pada populasi lansia. LSS dapat berupa kelainan kongenital ataupun kelainan yang didapat, dimana kebanyakan LSS diakibatkan oleh proses degeneratif. Diagnosis LSS melibatkan kombinasi dari temuan klinis dan radiologis. Tatalaksana pasien LSS dapat meliputi upaya konservatif berupa terapi fisik, injeksi steroid pada persendian facet ataupun ruang epidural, hingga tindakan operasi dekompresi. LSS seringkali menurunkan kualitas hidup serta produktivitas seseorang, sehingga LSS sering dijadikan sebagai indikasi untuk dilakukan prosedur operasi medula spinalis lumbal. Laporan kasus: Wanita, 41 tahun mengeluh nyeri punggung bawah serta nyeri yang menjalar ke bokong dan tungkai kiri, yang disertai sensasi kebas pada tungkai kiri sisi antero-lateral. Keluhan dirasakan terus menerus sejak 5 bulan lalu. Pemeriksaan fisik di dapatkan Visual Analogue Scale (VAS): 5-6, tes laseque positif tungkai kiri serta hipoestesia pada dermatom L4, L5 dan S1. Temuan MRI lumbal mengarah kepada diagnosis stenosis kanalis L4-L5 dan L5-S1. Dilakukan laminektomi dan Posterior Lumbar Interbody Fusion (PLIF). Kesimpulan: Pemilihan modalitas bedah didasarkan pada lokasi anatomis, jumlah segmen, keterlibatan thoracolumbar junction, adanya anatomi transisional, instabilitas, ataupun deformitas. Beberapa faktor yang mempengaruhi luaran klinis pasien pasca prosedur operasi perlu menjadi pertimbangan sebelum memulai tindakan bedah.